The last playboy the high life of Porfirio Rubirosa - Levy, Shawn 1961- (Fourth Estate, 2005)
Porfirio Rubirosa was the last great playboy: a symbol of powerful masculinity, ubiquity, and easy-come-easy-go money. He had an eye for beautiful women, particularly when they came with great wealth: he managed to marry two of the richest women on the planet. Rumor had him bedding hundreds of others, including Christina Onassis, Eva Perón, and Zsa Zsa Gabor. But he was a man's man, too, chumming around with the likes of Joe Kennedy, Frank Sinatra, Oleg Cassini, Aly Khan, and King Farouk. When above-board income was scarce, he diverted himself with jewel-thievery, shadowy diplomatic errands, and any other illicit scam that came his way. Whatever legitimate power he wielded came to him from Rafael Trujillo, one of the most power-mad dictators the New World has ever seen. When Rubi died at the age of 56, wrapping his sports car around a tree, an era went with him.--From publisher description.
Keywords: Rubirosa, Porfirio -- 1909-1965; Rubirosa, Porfirio -- 1909-1965 -- Relations with women; Diplomats -- Dominican Republic -- Biography; Biografie